Application of solar quiet (Sq) current in determining mantle conductivity-depth structure in Malaysia. (1st October 2019) - Abidin, Zamri Zainal; Jusoh, M.H.; Abbas, M.; Yoshikawa, A.
Abstract: The mantle electrical conductivity-depth structure of Malaysia was determined for the first time using solar quiet day ionospheric current (Sq) variations. Spherical harmonic analysis (SHA) was employed to separate the external and internal field contribution to the Sq variations. A transfer function was applied in estimating the conductivity-depth profile for the paired of external and internal coefficients of the SHA. We observed a downward increase in electrical conductivity with initial magnitude of 0.0065 S/m at a depth of ∼ 56 km which gradually rose to 0.0106 and 0.0140 S/m at 118 and 180 km. Subsequently, the conductivity profile rose to about 0.0228 S/m at 380 km (near the base of the upper mantle) and reached 0.0260 S/m at 435 km, after which a sharp steep increase was observed at 450 km with conductivity profile of 0.0278 S/m. Consequently, the conductivity profile increases significantly to about 0.1367 S/m at a depth of 973 km and reached its peak value 0.1975 S/m at the depth of 1097 km in the lower mantle with no indication of leveling off. An evidence of discontinuity was observed near 390–460 km and 675–746 km. A slight increase in conductivity values at depth between 150 and 300 km corresponds to the region of unusual global low velocity zone with high electrical conductivity. The conductivity profile showed a less steep increase above 450 km below which a steep increase was observed. The present profile showed the deepest penetration depth which may be attributed to the influence of equatorial electrojet current (EEJ) that is actively supported by the conductive properties of the Earth's interior within the study region. Highlights: The paper gave evidence to the idea that the deepest depth of penetration depth may be attributed to the influence of equatorial electrojet current (EEJ). The result from this study shows conductivity profile with less steep increase within the first few kilometers to a depth of about 400 km followed by a sharp steep increase to about 1100 km in the lower mantle. High conductivity values were observed at depth below 400 km, and the profiles exhibit relatively large lateral differences which we assumed depict structural differences in the conductivity beneath the continental regions.